Analisis Pengaruh Modal terhadap Operasional Kopkar Karya Bersama PT. Tasik Raja - Rani Andini; Ripho Delzy Perkasa (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Cooperatives as a form of business entity are certainly closely related to all forms of activity that are synonymous with capital. The purpose of this study was to determine the analysis of the effect of capital on cooperative operations. This research is a type of descriptive analysis research. Data collection techniques used were interviews, observations, and literature studies from several related journal sources. Based on research analysis results it was found that the effect of capital on cooperative operations has increased the productivity of cooperatives. Where, operational costs such as salaries and allowances, meeting costs and use of company assets have proven to be able to increase cooperative productivity which has an impact on increasing residual income from operations. Keywords : Cooperatives, Capital, Operational